Reciclagem de braquetes metálicos utilizando ácido fluorídrico a 10%: análise por meio de teste de resistência ao cisalhamento in vitro - Pompeo, Daniela Daunfenback (2013)
The purpose of this study was to evaluate the shear bond strength of resin/bracket interface of new and recycled brackets, treated in different ways. A total of 45 orthodontic brackets were randomly divided into three groups: 1) new brackets, 2) brackets recycled by etching 10% hydrofluoric acid for 60 seconds and 3) brackets sandblasted with aluminum oxide. The specimens were subjected to shear bond strength test in a universal testing machine Instron Model 4444. Statistical analysis was carried out with analysis of variance (ANOVA) and Tukey Test (p <0.01). The average shear bond strength was 10.54 (± 2.03) MPa, 4,17 (± 1,05) MPa, 8,83 (± 1,21) MPa for Group 1, 2 and 3, respectively. The differences between the groups were statistically significant (p <0.01). Groups 1 and 3 obtained values of shear strength above the minimum desirable for a good clinical performance. Sandblasting method of aluminum oxide is effective to recycle orthodontic brackets, however, the recycling technique by etching 10% hydrofluoric acid for 60 seconds is not efficient to be used clinically.